The Essential Factors and Trend Development of IoT Smart Box - Surjandy; Meyliana; Condrobimo, Andreas Raharto; Eka Widjaja, Henry Antonius; Atmadja, Wiedjaja; Susanto, Rudy; Sablan, Bruno (Indonesian Journal of Information Systems, 2023)
Boxes for drug storage are handy and essential and play a role in helping the healing process and support maintaining patient health regularly for a long time. SmartBox is not a new thing, but because of its importance, it, SmartBox continues to be developed to date according to the needs needed. In previous research, the formation of SmartBox was only for particular things. This study tries to unify the 17 papers obtained with the help of a publish and perish application which is then carried out a literature review and using the VosViewer application to get an overview of trend development and the essential factors or aspects in the formation of SmartBox and its development. In addition to getting the trend of SmartBox development, this research also finds seven essential factors that will be useful for Smartbox development. With this research, it hopes that it will facilitate the development of SmartBox in the future.